2011
DOI: 10.1016/j.ejca.2010.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Does pain intensity predict a poor opioid response in cancer patients?

Abstract: dictive factor of poor opioid response in advanced cancer patients, as suggested by a recent work.Methods: A secondary analysis of one-hundred-sixty-seven patients referred for treatment of cancer-related pain was conducted. Pain intensity at admission was recorded and patients were divided in three categories of pain intensity: mild, moderate and severe.Patients were offered a treatment with opioid dose titration, according to department policy. Data regarding opioid doses and pain intensity were collected af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…However, it has been reported that higher initial pain intensity merely reflects undertreatment of pain. 21,22 We have already reported undertreatment in the present study population, 10 and although 24.1% of this study cohort were PMI negative, this did not predict time to SPC. Moreover, the comparative changes in opioid use, opioid switching, and other therapeutic interventions between baseline and time of SPC, regardless of PMI status, suggest that resources were optimally applied in pursuit of SPC.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, it has been reported that higher initial pain intensity merely reflects undertreatment of pain. 21,22 We have already reported undertreatment in the present study population, 10 and although 24.1% of this study cohort were PMI negative, this did not predict time to SPC. Moreover, the comparative changes in opioid use, opioid switching, and other therapeutic interventions between baseline and time of SPC, regardless of PMI status, suggest that resources were optimally applied in pursuit of SPC.…”
Section: Discussionmentioning
confidence: 44%
“…19,20 However, there are conflicting reports regarding some classification features, particularly initial pain intensity in predicting time to reach SPC. 21,22 Furthermore, the operational definitions for various classification features of CP such as psychological distress and incident pain have presented interpretive challenges. 19,23 Consequently, further evaluation and clarification of the role of previously identified classification features of CP is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid opioid dose escalation in chronic pain patients could lead to the development of tolerance, although clinical assessment of opioid tolerance remains a challenge [21]. Some investigators have suggested that patients at higher risk may experience more subjective pain, making it even more difficult to adequately assess the clinical effectiveness of opioid therapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…A high level of pain intensity “per se”, however, does not seem to be clinically an intrinsic factor, as it may possibly depend on several factors. For example, it may result from a previous undertreatment, which could be potentially resolved in a simple way and could not influence the prognosis . The multicenter nature of the study, with unselected settings using different procedures of opioid titration and no clear definition of some variables, could have influenced the data.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it may result from a previous undertreatment, which could be potentially resolved in a simple way and could not influence the prognosis. 6 The multicenter nature of the study, with unselected settings using different procedures of opioid titration and no clear definition of some variables, could have influenced the data. For instance, original data suggested a delayed recourse to strong opioids in a substantial percentage of patients.…”
Section: Introductionmentioning
confidence: 99%